Patient-centric implementation of an electronic medication management system at a tertiary hospital in Western Sydney. Issue 3 (1st July 2018) - Gunja, Naren; Dunlop, Ian; Vaghasiya, Milan; Kuan, Kevin; Poon, Simon
Abstract : Background: Traditional implementations of electronic medication management (EMM) systems have involved two common formats – a 'big bang' approach on the day of go-live, or a phased ward-by-ward approach over months. Objective: To describe the patient-centric roll-out, a novel implementation model in converting from paper to EMM. Method: This model iteratively converted a large tertiary teaching hospital to electronic from paper medication charts, commencing the roll-out in the emergency department (ED). The tenet of 'one patient, one chart' was maintained with new patients commenced on EMM, while existing inpatients were maintained on paper charts until their discharge. In the second week, all other intake points commenced patients on EMM, and in the third week, all remaining patients were manually converted to EMM. The implementation was assessed with training completion rates, staff satisfaction surveys, focus group interviews and incident logs. Results: At go-live, 79% of doctors, 68% of nurses and 90% of pharmacists were trained in the EMM system. The ED converted to electronic prescribing within 24 hours; by day 20, all patients were on EMM. Two hundred and thirty issues were logged, none critical, of which 22 were escalated. Of the 51, 063 medications administered, there were 13 EMM-related clinical incidents including three double dosing errors, none of which led to an adverse event or death. Overall, 77% of staff surveyed were satisfied with the EMM implementation. Conclusions: The patient-centric roll-out model represents an innovative and safe approach with a single medication chart reducing transcription and improved medication safety for the patient and the organisation.